An exploration of the state of mind of Malaysia jazz practitioners: decision-making in improvisation / Nur Syahirah Badrulhisam - Badrulhisam, Nur Syahirah (2022)
The purpose of this study is to examine how Malaysian Jazz Practitioners make decisions on jazz improvisations, focusing on the state of mind and the process by which it was created. Objectively this study is to explore the state of mind on making decisions in jazz improvisation. Data were collected based on interviews of six Jazz Practitioners in Malaysia, Mr. Benjamin Lee Soon Loong, Mr. Eddy Lim, Part-time saxophone lecturer in Uitm, Dr. Yeoh Pei Ann, Coordinator of Degree in Music Performance of Uitm, Mr. Jeffny, and Mr. Syed Harith Daniel, full-time jazz saxophonist, Mr. Ihzwan Omar, also known as Iju. The analysis provided greater visibility towards the state of mind of Malaysian Jazz Practitioners and the decision-making on the improvisational part. Hopefully, the evidence about this research will be a substantial contribution and guidelines for beginners and intermediate musicians.